ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF NURSE IN MUFID ACEH GENERAL HOSPITAL - Putri Ilham Sari; Adang Bachtiar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: To improve the human resources of the hospital, one of nurses to ensure the hospital service is well organized, the hospital management must have good strategy management.This research was conducted at Mufid Aceh General Hospital to get an overview of the factors that affect the performance of nurses at Mufid Aceh General Hospital. Methods: It was a qualitative research focused on employment documents, income documents, monthly staff satisfaction, monthly performance results nursing, patient satisfaction in Mufid Aceh General Hospital. Results: Internal factors that affect the low performance of nurses at Mufid Aceh General Hospital are satisfaction, work-related stress factors, short working period and low work motivation. While External factors that affect the low performance of nurses is work load factor. Conclusions: Based on the result of this research, it is suggested to Mufid Aceh General Hospital to planning of nurse requirement well, to make policy about income, to make job description and authority in accordance with competence of nurse staff and creating a retention program.